Layer-specific pain relief pathways originating from primary motor cortex - Gan, Zheng; Gangadharan, Vijayan; Liu, Sheng; Körber, Christoph; Tan, Linette Liqi; Li, Han; Oswald, Manfred; Kang, Juhyun; Martín-Cortecero, Jesús; Männich, Deepitha; Groh, Alexander; Kuner, Thomas; et al. (Science, 2022)
The primary motor cortex (M1) is involved in the control of voluntary movements and is extensively mapped in this capacity. Although the M1 is implicated in modulation of pain, the underlying circuitry and causal underpinnings remain elusive. We unexpectedly unraveled a connection from the M1 to the nucleus accumbens reward circuitry through a M1 layer 6-mediodorsal thalamus pathway, which specifically suppresses negative emotional valence and associated coping behaviors in neuropathic pain. By contrast, layer 5 M1 neurons connect with specific cell populations in zona incerta and periaqueductal gray to suppress sensory hypersensitivity without altering pain affect. Thus, the M1 employs distinct, layer-specific pathways to attune sensory and aversive-emotional components of neuropathic pain, which can be exploited for purposes of pain relief.